Targeting Inflammatory Responses to Streptococcus pneumoniae. Issue 6 (September 2015) - Periselneris, Jimstan; José, Ricardo J.; Brown, Jeremy
Abstract: Streptococcus pneumoniae is a common cause of infectious morbidity and mortality, causing otitis media, pneumonia, septicaemia, and meningitis. The host inflammatory response is required for clearance of bacteria, but excessive inflammation can mediate bystander tissue damage. The host response is complex; involving initial recognition by pattern recognition receptors, clearance by tissue macrophages and the institution of an inflammatory response. This is orchestrated by the synthesis of a range of cytokines and chemokines that mediate both local and distant inflammatory effects. This causes neutrophil recruitment, upregulation of mucosal immunity, an acute phase response, and eventually the generation of antibodies. Currently, apart from antibiotic initiation, the use of adjuncts is limited to steroids in meningitis, with less evidence for their use in pneumonia. Some antibiotics used in recommended treatment regimens have immunomodulatory effects which may explain their beneficial effects above and beyond their antibacterial functions. By understanding the role of inflammation in pathogenesis better, more targeted approaches are being developed to limit excessive inflammation. Pathways being evaluated include inhibition of chemokines, inhibition of coagulation pathways that crosstalk with inflammatory signalling, and possibly the repurposing of statins to take of advantage of their immunomodulatory effects. All these approaches much strike the balance of reducing excessive inflammation while allowing enough phagocyte recruitment to enable effective bacterial clearance. Focal Points: Bedside: Targeted inhibition of inflammatory pathways may be a useful adjuvant to antibiotic therapy of S. pneumoniae pneumonia and meningitis, to ameliorate host induced tissue damage. Nuance approaches may yield more benefit than broad brush immunosuppression, such as with corticosteroids. Benchside: The dissection of the complex interaction of pathways downstream of S. pneumoniae recognition will allow targeting of specific components of the inflammatory response. This will allow enough inflammation to control bacterial replication, but limit bystander tissue damage. Industry: Several drugs have been trialled for use in sepsis and pneumonia trials to control excessive inflammation that may be effective against S. pneumoniae induced disease. By identifying more effective targets, and identifying the cause of infection early, there is the potential to develop drugs that have therapeutic benefit.